Factors affecting to the cse investor's perception: a case of north central province - Wijekumara, J.M.N.; Madhushanka, D.M.T. (University of Jaffna, 2019)
The aim of this study is to identify the factors that affect to the perception of investors for investing in Colombo Stock Exchange special reference to the North Central Province.In the present study, three independent variables and one dependent variable are considered. A sample size of sixty individual investors was drawn from the population of North Central Province’s individual investors by using stratified random sampling method. The structured questionnaire was used to collect the data and the study used descriptive analysis, correlation analysis and regression analysis as the analytical tools. Result of the study revealed that socioeconomic status and savings have significant impact on perception of investors and awareness has insignificant impact on perception of investors for investing Colombo Stock Exchange. These results are implied to encourage investors and financial analyst to investing Colombo Stock Exchange by identifying factors that affected to their perception.
Keywords: Socioeconomic status; Awareness; Savings; Colombo stock exchange